Centrifuge Testing of Circular and Rectangular Embedded Structures with Base Excitations. Issue 3 (August 2019) - Seylabi, Elnaz Esmaeilzadeh; Agapaki, Eva; Pitilakis, Dimitris; Brandenberg, Scott; Stewart, Jonathan P.; Taciroglu, Ertugrul
We present data and metadata from a centrifuge testing program that was designed to investigate the seismic responses of buried circular and rectangular culverts. The specimen configurations were based on Caltrans Standard Plans, and the scope of research was to compare the experimental findings with the design method described in the NCHRP Report 611 as well as to formulate preliminary recommendations for Caltrans practice. A relatively flexible pipe and a stiff box-shaped specimen embedded in dense sand were tested in the centrifuge at the Center for Geotechnical Modeling at University of California, Davis and were subjected to a set of broadband and harmonic input motions. Responses were recorded in the soil and in the embedded structures using a dense array of instruments. Measured quantities included specimen accelerations, bending strains, and hoop strains; soil accelerations, shear-wave velocities, settlements, and lateral displacements; and accelerations of the centrifuge's shaking table. This data paper describes the tests and summarizes the generated data, which are archived atDesignSafe.ci.org (DOI: 10.17603/DS2XW9R) and are accessible through an interactive Jupyter notebook.